Răspunsuri

2014-04-23T23:58:35+03:00
X + 5 (x² -8x +16) -4(x² -6x +9) = 4x² -20 x +25 -3 ( 4 -4x +x²) +10
x + 5x² - 40 x +80 -4x² +24x - 36 = 4x² -20x +25 - 12 + 12x -3x² +10
x² - 15x +44 = x² -8x +23
x²-x² -15x +8x= 23 -44
-7x = -21
7x = 21
x = 21/7
x=3
2 5 2
2014-04-24T00:46:14+03:00
X + 5 (x² -8x +16) -4(x² -6x +9) = 4x² -20 x +25 -3 ( 4 -4x +x²) +10
x + 5x² - 40 x +80 -4x² +24x - 36 = 4x² -20x +25 - 12 + 12x -3x² +10
x² - 15x +44 = x² -8x +23
x²-x² -15x +8x= 23 -44
-7x = -21
7x = 21
x = 21/7
x=3

Cum a facut si Andrei.